Chemical Modifications Mark Alternatively Spliced and Uncapped Messenger RNAs in Arabidopsis. Issue 11 (11th November 2015) - Vandivier, Lee E.; Campos, Rafael; Kuksa, Pavel P.; Silverman, Ian M.; Wang, Li-San; Gregory, Brian D.
Abstract : Global identification of RNA modifications that affect the Watson-Crick base-pairing edge across the Arabidopsis transcriptome provides insights into the many functions of these important additions. Abstract: Posttranscriptional chemical modification of RNA bases is a widespread and physiologically relevant regulator of RNA maturation, stability, and function. While modifications are best characterized in short, noncoding RNAs such as tRNAs, growing evidence indicates that mRNAs and long noncoding RNAs (lncRNAs ) are likewise modified. Here, we apply our high-throughput annotation of modified ribonucleotides (HAMR ) pipeline to identify and classify modifications that affect Watson-Crick base pairing at three different levels of the Arabidopsis thaliana transcriptome (polyadenylated, small, and degrading RNAs). We find this type of modifications primarily within uncapped, degrading mRNAs and lncRNAs, suggesting they are the cause or consequence of RNA turnover. Additionally, modifications within stable mRNAs tend to occur in alternatively spliced introns, suggesting they regulate splicing. Furthermore, these modifications target mRNAs with coherent functions, including stress responses. Thus, our comprehensive analysis across multiple RNA classes yields insights into the functions of covalent RNA modifications in plant transcriptomes.